2019
DOI: 10.1016/j.jaci.2019.03.002
|View full text |Cite
|
Sign up to set email alerts
|

Immunodeficiency and EBV-induced lymphoproliferation caused by 4-1BB deficiency

Abstract: Background: The tumor TNF receptor family member 4-1BB (CD137) is encoded by TNFRSF9 and expressed on activated T cells. 4-1BB provides a costimulatory signal that enhances CD8 1 T-cell survival, cytotoxicity, and mitochondrial activity, thereby promoting immunity against viruses and tumors. The ligand for 4-1BB is expressed on antigen-presenting cells and EBV-transformed B cells. Objective: We investigated the genetic basis of recurrent sinopulmonary infections, persistent EBV viremia, and EBVinduced lymphopr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
62
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(65 citation statements)
references
References 39 publications
3
62
0
Order By: Relevance
“…Furthermore, we recently identified a familial form of CAEBV caused by digenic loss‐of‐function mutations in CD137 and PIK3CD (Rodriguez et al, submitted for publication). We showed that PIK3CD deficiency was associated with increased T cell proliferation (which might provide a cellular context for the maintenance of EBV‐infected T cells), while CD137 deficiency leads to impaired expansion of EBV‐reactive T cells (as observed in recently described CD137‐deficient patients) . These observations suggest that the pathways involved in the immune control of EBV‐infected B cells and EBV‐infected T cells may not be that different.…”
Section: The Genetic Basis Of Caebv and T/nk Lpdssupporting
confidence: 62%
See 2 more Smart Citations
“…Furthermore, we recently identified a familial form of CAEBV caused by digenic loss‐of‐function mutations in CD137 and PIK3CD (Rodriguez et al, submitted for publication). We showed that PIK3CD deficiency was associated with increased T cell proliferation (which might provide a cellular context for the maintenance of EBV‐infected T cells), while CD137 deficiency leads to impaired expansion of EBV‐reactive T cells (as observed in recently described CD137‐deficient patients) . These observations suggest that the pathways involved in the immune control of EBV‐infected B cells and EBV‐infected T cells may not be that different.…”
Section: The Genetic Basis Of Caebv and T/nk Lpdssupporting
confidence: 62%
“…TNFRSF9 deficiency was reported very recently in two patients with chronic EBV viremia, B‐cell lymphoma, and HLH . Like CD27, TNFRSF9 (also known as 4‐1BB or CD137) is a member of the TNFRSF family.…”
Section: Immunodeficiencies Causing Ebv‐driven B‐lymphoproliferative mentioning
confidence: 99%
See 1 more Smart Citation
“…The mutation abolished surface expression of CD137 on activated T cells, resulting in a diminished proliferation, IFN-γ secretion, perforin expression and a reduced cytotoxic activity of CD8 + T cells upon stimulation with allogeneic and human leukocyte antigen (HLA)-matched EBV-transformed B cells. 8 Somekh et al analyzed four different patients with four distinct homozygous mutations in CD137 that reduced or abolished CD137 expression. Defects were seen in T cell activation and in the diversity of the TCR repertoire.…”
mentioning
confidence: 99%
“…10 Two of the four patients analyzed by Somekh et al suffered from an EBV-related B cell lymphoma, Hodgkin's lymphoma (HL) and Burkitt's lymphoma, respectively, and one patient described by Alosaimi et al presented with HL. 8,9 One patient analyzed by Rodriguez et al suffered from EBV-associated T cell lymphoproliferative disease, and finally succumbed to hemophagocytic lymphohistiocytosis (HLH). 10 Thus, a common denominator of the three studies is that mutations in CD137 facilitate EBV-associated diseases, implying that under normal conditions CD137 limits EBV in causing pathology.…”
mentioning
confidence: 99%